Palmitoleic and Dihomo-γ-Linolenic Acids Are Positively Associated With Abdominal Obesity and Increased Metabolic Risk in Children - Hua, Man-Chin; Su, Hui-Min; Lai, Ming-Wei; Yao, Tsung-Chieh; Tsai, Ming-Han; Liao, Sui-Ling; Lai, Shen-Hao; Huang, Jing-Long (Frontiers in Pediatrics, 2021)
Background: The impact of abdominal obesity (AO) on plasma fatty acid changes and cardiometabolic risk in children who are obese and overweight has rarely been investigated. This study determined whether plasma fatty acid composition differed between children with AO and those without AO and its relationship with metabolic risk, particularly in the obese and overweight groups. Methods: A total of 181 schoolchildren (aged 7–18 years) were included. Anthropometric and biochemical data and plasma fatty acid profiles were analyzed, and the indices of desaturase activity were estimated. Children were categorized based on their body weight and AO status. A continuous metabolic risk score was calculated using the sum of the z-scores of metabolic variables. A one-way analysis of variance test was used to compare the composition ratio of fatty acids between children with and without AO in the obese and overweight groups and normal-weight controls. Pearson analysis was also used to explore significant fatty acid and desaturase indicators associated with metabolic abnormalities. Results: Children who were obese and overweight (N = 126) displayed higher dihomo-γ-linolenic acid (20:3n-6) and γ-linolenic acid (18:3n-6) proportions than normal-weight controls (N = 55), but lower heptadecanoic acid (17:0) proportion, regardless of the AO status of each individual. Obese and overweight children with AO (N = 89), but not their non-AO counterparts (N = 37), exhibited a significantly higher proportion of palmitoleic acid (16:1n–7) than the remaining study groups. Pearson analysis showed that high proportions of palmitoleic acid and dihomo-γ-linolenic acid, as well as increased stearoyl-coenzyme A desaturase-1(16) and delta-6 desaturase and decreased delta-5 desaturase activities, are strongly correlated with weight-height ratio, homeostasis model of assessment values for insulin resistance, hypertriglyceridemia, and continuous metabolic risk scores. Conclusion: Higher palmitoleic acid and dihomo-γ-linolenic acid proportions, as well as increased stearoyl-coenzyme A desaturase-1(16) and delta-6 desaturase and decreased delta-5 desaturase activities are associated with AO and increased metabolic risk in children who are obese and overweight.